An Analysis of Fill Factor Loss Depending on the Temperature for the Industrial Silicon Solar Cells - Kwan Hong Min; Taejun Kim; Min Gu Kang; Hee-eun Song; Yoonmook Kang; Hae-Seok Lee; Donghwan Kim; Sungeun Park; Sang Hee Lee (Energies, 2020)
Since the temperature of a photovoltaic (PV) module is not consistent as it was estimated at a standard test condition, the thermal stability of the solar cell parameters determines the temperature dependence of the PV module. Fill factor loss analysis of crystalline silicon solar cell is one of the most efficient methods to diagnose the dominant problem, accurately. In this study, the fill factor analysis method and the double-diode model of a solar cell was applied to analyze the effect of J01, J02, Rs, and Rsh on the fill factor in details. The temperature dependence of the parameters was compared through the passivated emitter rear cell (PERC) of the industrial scale solar cells. As a result of analysis, PERC cells showed different temperature dependence for the fill factor loss of the J01 and J02 as temperatures rose. In addition, we confirmed that fill factor loss from the J01 and J02 at elevated temperature depends on the initial state of the solar cells. The verification of the fill factor loss analysis was conducted by comparing to the fitting results of the injection dependent-carrier lifetime.